Analisis Inflasi dan Bi 7-Day (Reverse) Repo Rate terhadap Return on Assets (RoA) pada PT Ace Hardware Indonesia, Tbk - Setiadi, Vieri Adha; Rosalina, Resmi Ranti (Research and Strategic Studies Center (Pusat Riset dan Kajian Strategis) Fakultas Syariah IAI Nasional Laa Roiba, 2024)
This study analyzes the relationship between inflation and the BI 7-day repo rate with ROA. Using secondary data for the period December 2017 to December 2021 from the website of PT. Indonesia Stock Exchange (IDX). Through the T test, F test and test the coefficient of determination using the SPSS version 26 application. In this study based on the conclusions obtained that the sign.f value is 0.001 <0.005 then Ho is rejected, this means that the independent variables affect ROA with an R2 test result of 99, 9% and the remaining 0.1% is influenced by external factors. this lesson. Thus there is a simultaneous effect of inflation and the BI 7-Day Repo Rate on ROA.